2023
DOI: 10.3390/oxygen3020017
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Total Phenolic Content, Total Antioxidant Activity and In Vitro Digestibility of Novel Wheat Crackers Enriched with Cereal, Legume and Agricultural By-Product Flours

Abstract: Wheat-flour crackers represent a staple snack option, although they lack nutritional value. Agricultural by-products such as olive and grape seeds, cereals such as barley and legumes such as lupine and chickpea are rich in bioactive compounds; therefore, flours obtained from those could represent a better option for bakery products fortification. The purpose of the present study was the investigation of total phenolic content and antioxidant activity before and after the baking of wheat crackers enriched with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…The composition of the functional meals was the same as the control meal, except that they contained 55 gr of the enriched crackers (either 10% grape seed flour crackers or 40% barley flour crackers enriched with β-glucan, 3 pieces). The 10% grape seed flour crackers were formulated according to the recipe mentioned in a previous publication of our research team, whereas the 40% barley flour crackers were formulated using the recipe found in the same publication but with the addition of β-glucan in order to receive 3 gr β-glucan/3 crackers and meet the EFSA health claim [41]. Each meal weighed 165 g. The nutritional composition of the meals is shown in Table 1.…”
Section: Study Mealsmentioning
confidence: 99%
“…The composition of the functional meals was the same as the control meal, except that they contained 55 gr of the enriched crackers (either 10% grape seed flour crackers or 40% barley flour crackers enriched with β-glucan, 3 pieces). The 10% grape seed flour crackers were formulated according to the recipe mentioned in a previous publication of our research team, whereas the 40% barley flour crackers were formulated using the recipe found in the same publication but with the addition of β-glucan in order to receive 3 gr β-glucan/3 crackers and meet the EFSA health claim [41]. Each meal weighed 165 g. The nutritional composition of the meals is shown in Table 1.…”
Section: Study Mealsmentioning
confidence: 99%
“…Wheat crackers are rich in starch but poor in dietary fiber and antioxidants; as a result, their nutritional composition is not well balanced [Ujong et al, 2023]. and antioxidants from by-product flours of the agri-food industry to improve their health effects [Chatziharalambous et al, 2023].…”
Section: Introductionmentioning
confidence: 99%